Bioflocculation management through high-rate contact-stabilization: A promising technology to recover organic carbon from low-strength wastewater. (1st November 2016) - Rahman, Arifur; Meerburg, Francis A.; Ravadagundhi, Shravani; Wett, Bernhard; Jimenez, Jose; Bott, Charles; Al-Omari, Ahmed; Riffat, Rumana; Murthy, Sudhir; De Clippeleir, Haydée
Abstract: A series of pilot-scale studies were performed to compare conventional high-rate activated sludge systems (HRAS) (continuous stirred tank reactor (CSTR) and plug flow (PF) reactor configurations) with high-rate contact-stabilization (CS) technology in terms of carbon recovery potential from chemically enhanced primary treatment effluent at a municipal wastewater treatment plant. This study showed that carbon redirection and recovery could be achieved at short solids retention time (SRT). However, bioflocculation became a limiting factor in the conventional HRAS configurations (total SRT ≤ 1.2 days). At a total SRT ≤1.1 day, the high-rate CS configuration allowed better carbon removal (52–59%), carbon redirection to sludge (0.46–0.55 g COD/g CODadded ) and carbon recovery potential (0.33–0.34 gCOD/gCODadded ) than the CSTR and PF configurations (28–37% COD removal, carbon redirection of 0.32–0.45 g COD/g CODadded and no carbon harvesting). The presence of a stabilization phase (famine), achieved by aerating the return activated sludge (RAS), followed by low dissolved oxygen contact with the influent (feast) was identified as the main reason for improved biosorption capacity, bioflocculation and settleability in the CS configuration. This study showed that high-rate CS is a promising technology for carbon and energy recovery from low-strength wastewaters. Graphical abstract: Highlights: High carbon redirection can be achieved by applying short SRT. Minimum oxidation of COD is needed to produce EPS for efficient solids separation. RAS aeration in HR-CS play a key role for improved biosorption. Feast-famine in HR-CS play a key role for improved bioflocculation & carbon recovery. Improved carbon capture (59%) was achieved in HR-CS compared to conventional A-stages.